Analisis Perbandingan Model Prediksi Kebangkrutan Altman Z-Score dan Zmijewski di BEI Periode 2011 - 2015 - Nindya Ayu Damayanti; N. Nurhayati; Susanti Prasetyaningtyas (UPT Penerbitan Universitas Jember, 2019)
This study aimed to compare the use of bankruptcy prediction model Altman Z-Score and Zmijewski on delisting companies on the Stock Exchange the period 2011 - 2015. The study population is a company delisting from the Stock Exchange in the period 2011-2015. The sample consists of 7 companies using method. purposive sampling Secondary data used in the form of financial statements of companies that issued from stock for bankruptcy in the period 2011-2015. The data analysis in this research is to perform the calculation of financial ratios in each sample, according to the variables of bankruptcy prediction model were compared to the model of Altman Z-Score and Zmijewski. Furthermore, the company classifies conditions appropriate point cut-off of each model and did calculations the accuracy of each model. Keywords: Altman Z-Score, Delisting, Bankruptcy, Zmijewski.